Serial pulmonary function tests in progressive systemic sclerosis. - Bagg, L R (1979)
Serial pulmonary function tests were performed on nine patients with progressive systemic sclerosis over a mean period of ten years. Abnormality was seen to develop both early and late in the course of the disease, and the earliest abnormality observed was impairment of the transfer factor. Deterioration of some aspect of pulmonary function was noted in each case, evidence of restriction or air trapping being seen with equal frequency. Two patients died, both of causes unrelated to their pulmonary involvement, and even pronounced early involvement of the lungs did not necessarily imply a bad prognosis.